Systemic governance and circular economy synergies: A multidimensional analysis of China's “Zero-waste Cities” initiative - Yushuang Li; Guijuan Shan; Shuoshuo Hao; Jian Li; Jinhui Li (Circular Economy)
China's “Zero-waste Cities” initiative, launched in 2018, represents a transformative strategy to address escalating solid waste challenges through systemic governance and circular economy principles. This study systematically examines the initiative's framework, including pilot project deployment, policy evolution, and scalability during the 14th Five-Year Plan (2021–2025). The phased implementation prioritized sector-specific models—industrial symbiosis, agricultural circularity, and smart municipal waste networks—to transition from risk control to green transformation. A SWOT analysis identifies strengths in centralized governance and technological innovation while highlighting challenges such as regional disparities in infrastructure and low market acceptance of recycled materials. Strategic recommendations emphasize data-driven governance, fiscal incentives for circular businesses, and cross-sector collaboration to bridge implementation gaps. This research underscores the initiative's dual impact: mitigating solid waste pressures and offering globally replicable insights. The framework provides a blueprint for sustainable urbanization, contributing actionable strategies to the United Nations Sustainable Development Agenda through scalable models of circular economy integration.